DESIGN, SYNTHESIS AND BIOLOGICAL EVOLUTION OF 3, 4-IHYDROSELENOPHENO [2,3-D]PYRIMIDINE SULFONAMIDES AS POTENTIAL ANTIMICROBIAL AGENTS - KOTAIAH. YALAGALA; VENKATA RAO. CHUNDURI (International Journal of Pharma and Bio Sciences, 2013)
In the present study, novel 3, 4–dihydroselenopheno[2,3-d]pyrimidine sulfonamides were designed, synthesized, characterized and screened for their antimicrobial activities. The synthetic routes followed for the preparation of designed compounds are starting from standard Gewald reaction. Further, the standard literature protocols are used for the reaction conditions and they were stabilized. The synthesized compounds were analyzed by spectral studies to confirm their structure. Then, they were studied for their in vitro antimicrobial activity bythe well diffusion method. A total of fifteen novel 3, 4–dihydroselenopheno[2,3-d]pyrimidine sulfonamides were synthesized, characterized and screened for their biological activities. Among the synthesized compounds 6a and 6c exhibited a significant activity toward both Gram-positive, Gram-negative bacteria MIC at 3.12 and 6.25 μg mL-1.. In addition these new agents, merit further studies to explore them as potential chemotherapeutics for antibacterial infections and for lead optimization to design a novel class of antibacterial agents.